THE INFLUENCE OF CATALYST AND FEEDSTOCK ON PRODUCT DISTRIBUTIONS FOR CRACKING OF c8 PARAFFINS ON HY AND HZSM-5 ZEOLITES - Zainurlis Zainuddin (Jurnal Kimia Terapan Indonesia, 1994)
Catalytic cracking of n-octane and 2-methylheptane, as well as mixtures of these paraffins, has been studied on HY and HZSAI-5 zeolites, and also on combinations of the catalysts. For cracking on individual zeolites, both feedstock and catalyst influence the resulting product distributions. For all feedstocks, product distributions are shifted towards smaller fragments for reaction on HZSM-5 compared to HY. Ratios of branched to linear paraffins are much more strongly influenced by catalyst type and feedstock than the corresponding ratios for olefinic products. For reactions on catalyst mixtures, distributions of the Iota I products by carbon number correspond well to a summation of contributions on the individual catalysts. However, a greater departure from prediction is seen for individual distributions of paraffins, olefins and aromatics, as well as for ratios of branched 10 lineal' paraffins, showing that hydrogen transfer processes and isomerization must occur. The addition of pentasil has also resulted in enrichment of the linear saturates at 101-,'ercarbon number which is due to preferential cracking of linear paraffins over the branched isomers.